Application of Piezoceramics in Relays. (1976) - Guntersdorfer, M.; Kleinschmidt, P.; Veith, R.
Abstract : For the application of a piezoceramic as a d.c. electromechanical transducer to drive relay contacts the mechanical output energy is the most important feature. The energy has been calculated as a function of the applied electric field strength for longitudinal and transverse operation. For a typical ceramic material maximum values of 53 mWs/cm 3 (long.) and 21 mWs/cm 3 (trans.) are obtained, taking into account large signal behaviour. Conventional bending elements, which are used to achieve higher deflections at lower voltages, show transformation losses caused by inhomogeneous stress distribution, energy storage in the metal part and inactive bending modes. On the other hand by utilizing the effects of transverse clamping and stiffness compensation, the output energy can be increased by more than one decade as experimentally verified with some special types of highly efficient bending elements. A delayed action relay showing low temperature and shock sensitivity has been tested over more than 10 000 switching cycles.